The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/978-3-642-11615-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Computer Simulation Tool for Application in Adolescent Spinal Deformity Surgery

Abstract: Abstract. Scoliosis is a three-dimensional spinal deformity which requires surgical correction in progressive cases. In order to optimize correction and avoid complications following scoliosis surgery, patient-specific finite element models (FEM) are being developed and validated by our group. In this paper, the modeling methodology is described and two clinically relevant load cases are simulated for a single patient. Firstly, a pre-operative patient flexibility assessment, the fulcrum bending radiograph, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In previous studies we have described the patient-specific modelling methodology for a single scoliosis patient undergoing a pre-operative flexibility test [31], and shown good agreement between predicted and clinical correction for a single patient undergoing anterior scoliosis surgery [30], but this study extends the previous work to compare predicted and actual surgical correction for a group of six AIS patients.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In previous studies we have described the patient-specific modelling methodology for a single scoliosis patient undergoing a pre-operative flexibility test [31], and shown good agreement between predicted and clinical correction for a single patient undergoing anterior scoliosis surgery [30], but this study extends the previous work to compare predicted and actual surgical correction for a group of six AIS patients.…”
Section: Discussionmentioning
confidence: 69%
“…Our work in this field to date has developed a patient-specific modelling methodology in which model anatomy is derived from pre-operative low-dose-computed tomography (CT) scans. This methodology was recently applied to simulate anterior surgical correction for a single patient, finding that the predicted post-operative surgical correction agreed with the clinical value [30]. However, it is not clear from a single patient what the relative importance of patient-specific anatomy and patient-specific tissue properties is in correctly predicting surgical correction.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the corrective forces acting at each screw were difficult to measure since the rotating device is attached only to the implant rod. The magnitude of forces occurring at each screw is also important because overloading due to the rod rotation maneuver might occur (Little and Adam, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our method for deriving patient‐specific FE models from low‐dose CT scan data has been previously described 30, 31. CT is not normally performed clinically, however Kamimura et al 32 showed that pre‐operative CT allowed safer screw sizing and positioning for thoracoscopic (keyhole) anterior surgery approaches.…”
Section: Methodsmentioning
confidence: 99%